2006
DOI: 10.1093/ilar.47.4.326
|View full text |Cite
|
Sign up to set email alerts
|

Selection, Acclimation, Training, and Preparation of Dogs for the Research Setting

Abstract: Dogs have made and will continue to make valuable contributions as animal models in biomedical research. A comprehensive approach from time of breeding through completion of in-life usage is necessary to ensure that high-quality dog models are used in studies. This approach ensures good care and minimizes the impact of interanimal variability on experimental results. Guidance related to choosing and developing high-quality laboratory dogs and managing canine research colonies is provided in this article. Ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…However, it is presumed that appropriate puppy-human interactions occurred during the critical neonatal period since these types of interactions are important to a dog's adaptability as a research subject (NRC 1992;Meuiner, 2006). Requirements for socialization (i.e., exposure to novel environmental and social stimuli in the first few weeks of life) for dogs used in research are generally the same as for working and pet dogs (Meunier, 2006;Scott and Fuller, 1965). These requirements typically include daily positive human handling, introduction to a variety of environmental sounds and textures, varying the people that interact with the puppy, and accustoming the puppy to medical examination procedures (e.g., touching head and neck, handling legs, touching paws, opening mouth, examining ears) (Meunier, 2006).…”
Section: Research Dogs and Housingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is presumed that appropriate puppy-human interactions occurred during the critical neonatal period since these types of interactions are important to a dog's adaptability as a research subject (NRC 1992;Meuiner, 2006). Requirements for socialization (i.e., exposure to novel environmental and social stimuli in the first few weeks of life) for dogs used in research are generally the same as for working and pet dogs (Meunier, 2006;Scott and Fuller, 1965). These requirements typically include daily positive human handling, introduction to a variety of environmental sounds and textures, varying the people that interact with the puppy, and accustoming the puppy to medical examination procedures (e.g., touching head and neck, handling legs, touching paws, opening mouth, examining ears) (Meunier, 2006).…”
Section: Research Dogs and Housingmentioning
confidence: 99%
“…Requirements for socialization (i.e., exposure to novel environmental and social stimuli in the first few weeks of life) for dogs used in research are generally the same as for working and pet dogs (Meunier, 2006;Scott and Fuller, 1965). These requirements typically include daily positive human handling, introduction to a variety of environmental sounds and textures, varying the people that interact with the puppy, and accustoming the puppy to medical examination procedures (e.g., touching head and neck, handling legs, touching paws, opening mouth, examining ears) (Meunier, 2006). While residing at the vendor's facility dogs were pair-housed, grouped by gender, body size, and compatibility from weaning through adulthood.…”
Section: Research Dogs and Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…Puppies are curious about novel situations, but they can readily develop fear behaviors early in their exposure periods. Studies on research dogs have shown that handling for 3 minutes per day and exposure to stressors (e.g., changes in ambient temperature, different flooring, different handlers) in a manner that gradually increases in intensity and duration has positive effects on resistance to disease, emotional reactivity, and problem solving (Meunier, 2006). Gazzano et al (2008) reported that well-handled puppies of various breeds were calmer.…”
Section: Introduction Of Puppies To Potential Stressors Sensitive Permentioning
confidence: 99%
“…Positive human-dog interactions have been recommended in a number of reports (Hubrecht et al, 1992;Bayne, 2003;Joint Working Group on Refinement, 2004;Meunier, 2004) and by the European Convention ETS 123 (Council of Europe, 1986), and the implementation of such interactions is vital for the success of research projects and associated experiments. In view of the very limited interactions of the dogs of 2 research facilities with humans described by Hubrecht et al (1992), the present study aimed to characterize the behaviors of the laboratory dogs of 4 research facilities in Germany toward humans.…”
Section: Introductionmentioning
confidence: 99%